Pectins - Extraction, Purification, Characterization and Applications 2020
DOI: 10.5772/intechopen.84960
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Pectins

Abstract: Pectins and flavonoids are two related groups of important secondary metabolites derived from plants. The interaction between pectins and flavonoids can affect their shelf-life stability, functionality, bioavailability, and bioaccessibility. In this chapter, we will concentrate on the current opinions on the flavonoids to understand how to classify this group of secondary metabolites, what biological and pharmacological activities they possess, and how to biosynthesize them in plants. We will then discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Fan et al [ 36 ] demonstrated the anti-AChE activity of Rho. Additionally, Zhang et al [ 37 ] showed that Rho could inhibit a variety of important enzymes such as aggrecanase, aldose reductase, α-glucosidase, cholinesterase, protein tyrosine phosphatase and AChE, and tyrosinase. Our findings indicate, therefore, that Rho has the potential to improve cognitive dysfunction in Sco-induced amnesic zebrafish, probably by inhibiting AChE activity, as stated in the studies mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Fan et al [ 36 ] demonstrated the anti-AChE activity of Rho. Additionally, Zhang et al [ 37 ] showed that Rho could inhibit a variety of important enzymes such as aggrecanase, aldose reductase, α-glucosidase, cholinesterase, protein tyrosine phosphatase and AChE, and tyrosinase. Our findings indicate, therefore, that Rho has the potential to improve cognitive dysfunction in Sco-induced amnesic zebrafish, probably by inhibiting AChE activity, as stated in the studies mentioned above.…”
Section: Resultsmentioning
confidence: 99%